Determinants of stock price performance in the Indonesian basic industry - Novinda Krisna Putri; Dian Martha Nurul Amanah; Nurul Aini; Jenia Nur Soelistyoningrum (Journal of Enterprise and Development (JED), 2023)
Purpose — This study aimed to identify the determinant factors of the stock price performance, proxied by price earnings ratio, in the basic industry (IDXBASIC) and the causal relationship between them.Method — Data were collected from the Indonesia Stock Exchange for a period of five years, spanning from 2017 to 2021. The purposive sampling method was chosen, and a total of sixty firms were selected for the final sample of this study. This study adopts generalized least squares of panel data analysis using STATA version 13 software.Result — The results revealed that return on equity, debt-equity ratio, price-to-book value, earnings growth, and dividend payout significantly impact the price-earnings ratio (PE) and thus become significant determinants of the price-earnings ratio (PE). On the other hand, market return and firm size showed no significant influence on the price-earnings ratio.Contribution — This study's academic contribution is its specific focus on the Indonesia Basic Industry (IDXBASIC) and exploration of the factors influencing the Price-Earning Ratio (P/E ratio) within this sector, filling a significant gap in the literature and offering valuable insights for investors, policymakers, and market participants.